Advances in network complexity - Dehmer, Matthias, 1968-; Mowshowitz, Abbe; Emmert-Streib, Frank (Weinheim, Germany : Wiley-Blackwell, 2013)
A well-balanced overview of mathematical approaches to describe complex systems, ranging from chemical reactions to gene regulation networks, from ecological systems to examples from social sciences. Matthias Dehmer and Abbe Mowshowitz, a well-known pioneer in the field, co-edit this volume and are careful to include not only classical but also non-classical approaches so as to ensure topicality. Overall, a valuable addition to the literature and a must-have for anyone dealing with complex systems.
1. Functional complexity based on topology -- 2. Connections between artificial intelligence and conputational complexity and the complexity of graphs -- 3. Selection-based estimates of complexity unravel some mechanisms and selective pressures underlying the evolution of complexity in artificial networks -- 4. Three types of network complexity pyramid -- 5. Computational complexity of graphs -- 6. The linear complexity of a graph -- 7. Kirchhoff's matrix-tree theorem revisited: counting spanning trees with the quantum relative entropy -- 8. Dimension measure for complex networks -- 9. Information-based complexity of networks -- 10. Thermodynamic depth in undirected and directed networks -- 11. Circumscribed complexity in ecological networks -- 12. Metros as biological systems complexity in small real-life networks.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed July 24, 2013).
Keywords: Computational biology; Biomedical engineering -- Mathematical models; SCIENCE -- Life Sciences -- Biology; Biomedical engineering -- Mathematical models; Computational biology; Electronic books; Electronic books